2015
DOI: 10.1111/risa.12336
|View full text |Cite
|
Sign up to set email alerts
|

The Cry Wolf Effect and Weather‐Related Decision Making

Abstract: Despite improvements in forecasting extreme weather events, noncompliance with weather warnings among the public remains a problem. Although there are likely many reasons for noncompliance with weather warnings, one important factor might be people's past experiences with false alarms. The research presented here explores the role of false alarms in weather-related decision making. Over a series of trials, participants used an overnight low temperature forecast and advice from a decision aid to decide whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 44 publications
3
93
0
2
Order By: Relevance
“…Overload perception is when in a warning scenario, too much information is flowing simultaneously which may lead to irritation or confusion by the information consumers (formally known as the 'signal to noise' problem in perception and warning research). Hazard researchers have found that false alarms may alter decision-making, but that decisions are also contingent on the hazard scenario and the frequency of false warnings (Bliss, Dunn & Fuller, 1995;Dow & Cutter, 1998;LeClerc & Joslyn, 2015).…”
Section: Information Sources In Disastersmentioning
confidence: 99%
“…Overload perception is when in a warning scenario, too much information is flowing simultaneously which may lead to irritation or confusion by the information consumers (formally known as the 'signal to noise' problem in perception and warning research). Hazard researchers have found that false alarms may alter decision-making, but that decisions are also contingent on the hazard scenario and the frequency of false warnings (Bliss, Dunn & Fuller, 1995;Dow & Cutter, 1998;LeClerc & Joslyn, 2015).…”
Section: Information Sources In Disastersmentioning
confidence: 99%
“…The recursion is initiated with the terminal condition J S (x S , t) = 0 ∀t and J S (x, t) = ∞ ∀x = x S . Our constraints include departing by a time u that satisfies (4), choosing an allowable plant configuration (5), and only traversing along feasible safe nodes and edges in the network (6), (7). When the costs are deterministic, (3) may be written in forward form as…”
Section: A Deterministic Problemmentioning
confidence: 99%
“…When the task is one of trying to optimize multiple objectives, humans are notoriously poor at decision making, especially if the task is dynamic and has inherent uncertainty [4]- [7]. Consequently, decision support tools are needed to collaboratively optimize routes by evaluating and recommending multiple courses of action (COAs) from which a navy planner can select one.…”
Section: Introductionmentioning
confidence: 99%
“…They are “damned if they do and damned if they don't.” If they take strong action based on the worst‐case scenario, perhaps based on a feeling that they are protecting the public, they will be criticized if things turn out to be much less serious. Furthermore, if this happens repeatedly, they are subject to the “cry wolf” syndrome, in which the public will no longer believe what they say in these kinds of circumstances . On the other hand, if they don't give sufficient attention to the worst‐case scenario, they will be severely criticized if it comes to pass.…”
mentioning
confidence: 99%
“…Furthermore, if this happens repeatedly, they are subject to the "cry wolf" syndrome, in which the public will no longer believe what they say in these kinds of circumstances. (26) On the other hand, if they don't give sufficient attention to the worst-case scenario, they will be severely criticized if it comes to pass.…”
mentioning
confidence: 99%